2012
DOI: 10.1097/phm.0b013e3182643c36
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Monitoring of Multilayer Inelastic Bandaging and the Effect of Padding in Breast Cancer–Related Lymphedema Patients

Abstract: The working pressure during exercising with a force of 50 Pa is approximately 10 mm Hg with a short-stretch bandage applied. Adding a pad increases both the resting and the working pressure and also seems to be effective in increasing volume reduction of the limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In the current study we adopted manual lymph drainage as a decongestive therapy and found that after 3 weeks of CDT treatment, life quality of patients achieved great improvement and that the detumescence of the middle segment of forearm (10 cm below transverse cubital crease) was better than that of the middle segment of upper arm (10 cm above transverse cubital crease) and of the superior segment of upper arm (20 cm above transverse cubital crease) with a significant difference, which was consistent with other related studies [8,9,13]. Some researchers performed manual lymph drainage on 6 patients with simple breast lymphedema and after 20 times of treatment the transverse diameter, vertical diameter and average diameter of breast steadily decreased at different times, and axillary web syndrome was cured.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study we adopted manual lymph drainage as a decongestive therapy and found that after 3 weeks of CDT treatment, life quality of patients achieved great improvement and that the detumescence of the middle segment of forearm (10 cm below transverse cubital crease) was better than that of the middle segment of upper arm (10 cm above transverse cubital crease) and of the superior segment of upper arm (20 cm above transverse cubital crease) with a significant difference, which was consistent with other related studies [8,9,13]. Some researchers performed manual lymph drainage on 6 patients with simple breast lymphedema and after 20 times of treatment the transverse diameter, vertical diameter and average diameter of breast steadily decreased at different times, and axillary web syndrome was cured.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple‐layer short‐stretch bandaging was applied after MLD to prevent the re‐accumulation of fluid in the lymphedematous extremity and to benefit from the muscle pump effect until the following day during the intensive phase of CDT. The characteristics of the short stretch bandages were high working pressure and low resting pressure . Active, repetitive, and nonresistive exercises of the lymphedematous arm after bandaging were performed to the patients to increase fluid mobilization and enhance the muscle pump effect .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies reported that CDT was an effective treatment method for BCRL . In contrast, there are few studies about the predictive factors for the effectiveness of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The 18 guidelines for preventing lymphedema proposed by the National Lymphedema Network (HLN) [8] included avoiding venous blood collection, infusion, and blood pressure measurement, wearing protective gloves when doing daily housework, keeping the upper limbs hygienic, avoiding injuries to the affected limbs and other suggestions. The therapists for lymphedema introduced the precautions of preventing lymphedema and self-management of limbs at home to the patients and their families.…”
Section: Self-management and Prevention Of Lymphedemamentioning
confidence: 99%